Identification of the thickness and depth of coal seams using the Schlumberger configuration geoelectric method in Petai Village, Singingi Hilir District, Kuantan Singingi Regency - Sherly Mutiara; Usman Malik; Hijrah Septia Anisa (Science, Technology and Communication Journal, 2024)
The identification of the thickness and coal seam depth using the Schlumberger configuration geoelectric method in Petai Village, Singingi Hilir District, Kuantan Singingi Regency, Riau Province has been investigated. This study aims to determine the subsurface structure and its depth. The method used in this study is the one-dimensional Schlumberger configuration geoelectric method by processing data using Software Progress. The data obtained are (I) and potential difference (V). The information on rock layers at the research site is obtained based on the data processing results. The resistivity value of rocks on track 1 ranges from 2,272.23 – 1,317.96 Ohm.m with a depth of up to 19.05 m. The lithology layers identified the resistivity values obtained for track 1 are sand and dry gravel. The resistivity value of the second trajectory ranges from 1,188.91 – 1,491.29 Ohm.m with a depth of up to 17,00 m. The lithology layers identified the resistivity values obtained for track 2 are topsoil, coal, and sandstone. The resistivity value of the third trajectory ranges from 4,986.17 – 347.81 Ohm.m with a depth of up to 11,43 m.  The lithology layers identified the resistivity values obtained for track 3 including sandstone, coal, and sand. The result of the interpretation of track 1, track 2, and track 3 obtained the subsurface layers and their depth at the research location.